On-field: The response of South African mainstream sports journalists toward fan vlogging on YouTube during the 2019 Rugby World Cup - Pather, Benedict (Stellenbosch : Stellenbosch University, 2022)
Thesis (MA)--Stellenbosch University, 2022.